Consumer control, dependency and satisfaction with online service. Issue 4 (12th September 2016) - Chan, Shiu Fai; Barnes, Bradley R.; Fukukawa, Kyoko
Abstract : Purpose: The purpose of this paper is to develop and test a new conceptual model in an online service context. The model focuses on an important, yet often neglected customer-oriented construct, i.e., user "control", which is embedded in consumer behaviour when accessing the internet. The study examines the relationship between control, online dependency, online encounter satisfaction and overall satisfaction. It explains the strategic implications surrounding customer control and online dependency as means for enhancing customer satisfaction. Design/methodology/approach: A questionnaire was developed drawing on a combination of existing and new measurement items for the constructs in question. The instrument was later pilot tested on two consecutive occasions ahead of the main survey. A random sample of Hong Kong banking consumers was approached and interviews were undertaken via telephone. The data were analysed via confirmatory factor analysis and structural equation modelling was used to test the hypotheses relating to the model. Findings: The findings reveal positive relationships between control and online dependency, and control and online encounter satisfaction. Meanwhile control, online dependency and online encounter satisfaction lead to overall satisfaction. Originality/value: This study proposes a counterintuitive argument that while online service customers gain control of the online service process, they become more dependent on it, and their control and dependency also lead to their satisfaction, at both the online service encounter level and corporate level. Drawing on the pertinent literature, this is the first study to examine the importance of two information system constructs, i.e., control and online dependency, as predictors of consumer psychological fulfilment, i.e., satisfaction. The findings confirm that control as an initiator and driver of customer satisfaction in an online context, and online encounter satisfaction, further contributes to overall satisfaction at the corporate level.